1997
DOI: 10.1111/j.1399-0004.1997.tb02507.x
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic evaluation of Tc‐99m‐low‐density lipoprotein (LDL) distribution in patients with Gaucher disease

Abstract: Gaucher disease (GD) is frequently associated with reduced plasma levels of low density lipoproteins, presumably due to increased catabolism of LDL. The purpose of this study was to determine the distribution of Tc‐99m LDL (Tc‐LDL) in Gaucher patients, and compare the findings to bone marrow distribution. Four patients with non‐neuropathic Gaucher disease (type 1) underwent baseline whole body imaging at 4 and 24 h after injection of dialyzed autologous LDL labeled with 10–20 mCi Tc‐99m‐pertechnetate. Three of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Taken together with the increased level of apo E, available data suggest a central role of the pathological glucosylceramide-laden macrophages in aberrant lipoprotein metabolism in GD. Consistent with this notion, imaging for sites of lipoprotein uptake in vivo in GD revealed increased uptake of LDL primarily in the spleen and bone marrow, sites of major accumulation of glucosylceramide-laden macrophages in GD (Lorberboym et al 1997). However, the site(s) of increased HDL uptake in vivo in GD is not known.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Taken together with the increased level of apo E, available data suggest a central role of the pathological glucosylceramide-laden macrophages in aberrant lipoprotein metabolism in GD. Consistent with this notion, imaging for sites of lipoprotein uptake in vivo in GD revealed increased uptake of LDL primarily in the spleen and bone marrow, sites of major accumulation of glucosylceramide-laden macrophages in GD (Lorberboym et al 1997). However, the site(s) of increased HDL uptake in vivo in GD is not known.…”
Section: Discussionmentioning
confidence: 65%
“…Both low-density lipoprotein (LDL) and high-density lipoprotein (HDL) appear to be enriched in glucosylceramide (Clarke 1981). Associated with this altered lipoprotein composition, there is profound hypolipidemia due to decreased number of lipoprotein particles, attributed to increased rates of catabolism (Ginsberg et al 1984; Le et al 1988; De Fost et al 2009; Lorberboym et al 1997). Moreover, cell types other than macrophages are involved in the development of GD, underscoring the necessity to develop a “biomarker basket” to monitor diverse aspects of GD beyond the macrophage system (Mistry et al 2010)…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of HDL cholesterol appears to be the key abnormality. Whereas there is evidence that hypercatabolism of LDL in GD may occur via the macrophage system, such evidence is lacking for HDL (Le et al 1988; Lorberboym et al 1997; Ginsberg et al 1984). Turnover studies of radio-labeled HDL in GD1 showed an increased fractional catabolic rate of apoA1, which may reflect increased reverse cholesterol transport to result in enhanced biliary cholesterol secretion (Le et al 1988; Thornton et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that increased lipoprotein catabolism was mediated via the activated macrophage system. However, the question of whether lipid flux through the hepatocyte is also abnormal has not been investigated (Le et al 1988; Lorberboym et al 1997; Ginsberg et al 1984). Finally, recent data suggest impaired insulin signaling in GD1 due to enrichment of lipid rafts harboring insulin receptors, with GM3 arising from accumulation of its precursor, GlcCer (Langeveld and Aerts 2009; Langeveld et al 2008).…”
Section: Introductionmentioning
confidence: 99%